Дослідження зв'язку та мобільного інтернету в швидкісних потягах - Жигло, С. В. (ХНУРЕ, 2024)
In today's world, high-speed trains are an important part of the transport infrastructure, but passengers often face mobile communication problems while traveling. At the moment, the relevance of this topic is justified by the broad interest of the state represented by the Ministry of Digital Transformation, the national carrier of goods and passengers JSC Ukrainian Railways, leading electronic communications operators, end users of electronic communications services, and the practical need to solve this problem. Current methods include the construction of new base stations on each "problematic" section of the railway, but this is not economically feasible, as it requires significant capital investment, and the revenue from services will not cover operating costs. This report is dedicated to analyzing the existing problems and developing new methods to improve the quality of mobile communications.
Keywords: інтернет в швидкісних потягах; high-speed train